Pengaruh sales growth, managerial agency cost, gender diversity, operating capacity, firm size dan likuiditas terhadap financial distress pada perusahaan sektor basic material periode 2019-2023 - Della Azhara Yusuf (Universitas Negeri Surabaya, 2025)
The objective of this investigation is to determine the impact of financial distress on sales growth, managerial agency costs, gender diversity, operating capacity, firm size, and liquidity of companies in the basic materials sector listed on the Indonesia Stock Exchange during the 2019-2023 period.The Altman Z-score is employed to quantify financial distress.The companies in the basic materials sector that were listed on the Indonesia Stock Exchange during the 2019-2023 period comprise the population of this study.A purposive sampling technique was implemented to generate a research sample of 36 companies.The analytical instrument used is STATA 17, and the data analysis technique employed is panel data regression.The findings indicate that financial distress is positively influenced by liquidity and gender diversity, while sales growth, managerial agency costs, operational capacity, and firm size do not have a significant impact on financial distress.Consequently, it is anticipated that organisations in the fundamental material sector will effectively manage their existing assets and make informed decisions regarding debt.Furthermore, it is recommended that companies prioritise gender diversity in their board of directors to mitigate financial distress and improve management efficiency.